2015
DOI: 10.1108/edi-01-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Think manager, think male? Heterosexuals’ stereotypes of gay and lesbian managers

Abstract: Purpose -The purpose of this paper is to extend the "think manager, think male" research paradigm by examining managerial stereotypes as a function of both gender and sexual orientation, thus comparing the similarity of managerial stereotypes against the stereotypes of male (heterosexual and gay) and female (heterosexual and lesbian) managers. Design/methodology/approach -In total, 163 heterosexual participants used the 92-item Descriptive Index attribute inventory to rate one of five target groups: successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 47 publications
(87 reference statements)
3
37
0
Order By: Relevance
“…In an experimental study, Liberman and Golom (2015) found that gay male leaders were seen to be less similar to the successful manager prototype than were heterosexual male or heterosexual female managers. Furthermore, lesbian leaders were thought to be moderately similar to the successful manager prototype.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental study, Liberman and Golom (2015) found that gay male leaders were seen to be less similar to the successful manager prototype than were heterosexual male or heterosexual female managers. Furthermore, lesbian leaders were thought to be moderately similar to the successful manager prototype.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Furthermore, lesbian leaders were thought to be moderately similar to the successful manager prototype. Although this in an important study in an underdeveloped area, Liberman and Golom (2015) did not assess the perceived leadership effectiveness of the gay and lesbian leaders, nor did they measure the homonegativity of the participants. Perceived leadership effectiveness is important because it provides a theoretically and practically important dimension upon which gay and lesbian leaders could be evaluated differently from their heterosexual counterparts.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…These negative perceptions of transgender people would seem to be incompatible with the leader prototype held by followers. Some indirect empirical evidence for this assertion comes from Liberman and Golom () who found that other stigmatized sexual minorities who are thought to have some of these same characteristics (gay men and lesbian women) were considered to be less prototypical of the “successful manager” than heterosexual men and women. As a result, we would expect that leaders disclosing a transgender identity would be evaluated less favorably than leaders who do not disclose a transgender identity.…”
Section: Study 1: Background and Hypothesesmentioning
confidence: 99%
“…For example, the disclosure of one's LGBT identity by one coworker to another coworker is likely to elicit different reactions than the disclosure of that same identity by a supervisor to a subordinate. One reason for this is that the stigma associated with LGBT identities may be incompatible with the normative expectations of the stigma holder's other roles and identities (Hoyt & Chemers, ; Liberman & Golom, ). Given the importance of understanding this process for stigma holders, nonstigma holders, and organizations there have been calls in the literature for more research in this area (Fassinger, Shullman, & Stevenson, ; Kulik et al, ; Sawyer, Thoroughgood, & Webster, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation